1947
DOI: 10.1073/pnas.33.6.171
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Substances from Basidiomycetes

Abstract: In a survey' conducted in this laboratory it was noted that 213 of the 332 species of Basidiomycetes studied produced substances that inhibited the growth of Staphylococcus aureus. Among the species that seemed worthy of further investigation was Pleurotus griseus.2 P. griseus grew with medium rapidity on a thiamine-peptone agar' and a modified Czapek-Dox agar to which corn steep solids had been added. It formed a pink pigment which diffused intio the agar. After the fungus had grown for one to several weeks, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

1947
1947
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 0 publications
0
29
0
1
Order By: Relevance
“…The latter naturally occurring antibiotic is a para-quinone with a perhydroanthracene core, which was first isolated in the 1940s from the basidiomycete, Pleurotus griseus. 9 Though pleurotin has been synthesized, 10 a multi-gram fermentation process using Hohenbuehelia atrocaerulea for supply of pleurotin to the NCI has been reported. 11 Pleurotin possesses antibacterial, 9 antifungal, 12 and anti-cancer activity, including inhibiting the hypoxia-induced factor (HIF-1α), a transcription factor associated with many aspects of tumor growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter naturally occurring antibiotic is a para-quinone with a perhydroanthracene core, which was first isolated in the 1940s from the basidiomycete, Pleurotus griseus. 9 Though pleurotin has been synthesized, 10 a multi-gram fermentation process using Hohenbuehelia atrocaerulea for supply of pleurotin to the NCI has been reported. 11 Pleurotin possesses antibacterial, 9 antifungal, 12 and anti-cancer activity, including inhibiting the hypoxia-induced factor (HIF-1α), a transcription factor associated with many aspects of tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…9 Though pleurotin has been synthesized, 10 a multi-gram fermentation process using Hohenbuehelia atrocaerulea for supply of pleurotin to the NCI has been reported. 11 Pleurotin possesses antibacterial, 9 antifungal, 12 and anti-cancer activity, including inhibiting the hypoxia-induced factor (HIF-1α), a transcription factor associated with many aspects of tumor growth. 13 The underlying pathway to much of this biological activity is pleurotin's ability to act as a potent inhibitor (IC 50 0.17 μM) of the thioredoxin (Trx)-thioredoxin reductase (TrxR) system.…”
Section: Introductionmentioning
confidence: 99%
“…F-11334A1 was earlier reported as an inhibitor of neutral sphingomyelinase. 36 Pleurotin was discovered as an anti-bacterial substance by Robbin et al 37 and (À)-epigallocatechin gallate was reported to have an anti-bacterial activity. 38 The relationship between the reported activities for these compounds and our current observation remains to be further studied.…”
Section: Resultsmentioning
confidence: 99%
“…Gillet (Pleurotaceae). Pleurotin, with a quinonoid skeleton, was isolated from P. griseus (Robbins et al, 1947) and shown to have antimicrobial properties and anticancer properties (Welsh et al, 2003). We were unable to prove the presence of any such chemical constituents in AqFrA-3.…”
Section: Discussionmentioning
confidence: 99%